Produksi Cider Rambutan (Nephelii Lappacei) Dengan Variasi Lama Fermentasi Dan Kecepatan Pengadukan Pada Tahap Fermentasi Asetat - Sally, Calvin Eliezer Immanuel; Antara, Nyoman Semadi; Triani, I Gusti Ayu Lani (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
Rambutan (Nephelii lappacei) is a tropical fruit cultivated in tropical countries. Recorded in the Central Statistics Agency, rambutan fruit production in Bali province will reach 19,107 tons in 2022 (BPS, 2022). Rambutan has the potential to be made into cider because it has a high sugar content, namely 15 grams per 100 grams (Sampurno, 2018). Cider is a fermented drink containing around 6.5-8% alcohol and 3-7% acetic acid based on apple juice (Caturryanti et al., 2008). Cider can also be made from rambutan fruit because rambutan fruit has the same characteristics as apples, namely having a high sugar content and organic acid content. This study was designed using a Randomized Block Design with a factorial pattern with two factors, the first factor is fermentation time and the second factor is the frequency of stirring in the acetic acid fermentation process. The first factor uses fermentation time with 3 variations, namely 2 days, 4 days and 6 days. The second factor is the speed of stirring using a shaker with 3 variations, namely 80 rpm, 100 rpm, and 120 rpm which are carried out throughout the acetic acid fermentation. The variables studied in the following research are ethanol content, sugar content, total acid, pH, and organoleptic tests. Their interactions have a significant effect on ethanol content, sugar content, total acid, and pH. The results showed that fermentation time and stirring speed significantly affected all observed variables, except color. The best treatment was obtained in fermentation for 6 days with a stirring speed of 80 rpm, producing cider with characteristics of ethanol content of 1.97 ± 0.02%, sugar content of 783.5 ± 0.7 mg / ml, total acid of 0,95 ± 0,021%, pH 3,2 ± 0,1, not sweet (1 ± 0), sour (4,7 ± 0), slightly bitter (2,1 ± 0,14). This study proposes a fermentation time of 6 days and a stirring speed of 80 rpm as optimal for producing rambutan cider with the